(untitled) (Journal of Laboratory Animal Science, 2024)
Investigations were carried out to study the effect of supplementation of jojoba meal (Simmondisa chinensis) on biochemical, haematological and thyroid hormone profile in broiler rabbits. A total of fourty New Zealand white rabbits (4 week old) were randomly allotted to four dietary treatment groups, comprising ten rabbits in each group. The control group (T0) was fed with complete feed with no jojoba oil meal and test groups were fed complete feed with 5, 15 and 25 per cent jojoba oil meal in T1, T2 and T3 groups, respectively. Hematology and serum biochemical profile indicated reduction in haemoglobin (Hb), packed cell volume (PCV) and total erythrocyte count (TEC) in T2 and T3 groups compared to T0 and T1groups on 30th day of study, while serum calcium, phosphorus, cholesterol and total protein were not affected. It was observed that serum tri-iodothyronine (T3) and thyroxin (T4) levels in jojoba meal treated rabbits were declined in dose-dependent manner due to thyrotoxicity. Toxicopathological lesions include infiltration of inflammatory cells (T1) or inter-follicular thyroiditis in rabbits fed jojoba meal @ either 15 (T2) or 25 % (T3).